Suppliers of Organic Food: Evidence From Sisli And Kartal Ecological Bazaars Of Istanbul - Cevahir Kaynakci, Selim Ayta, Ali Kemal Ayan, Ismet Boz, (International Journal of Scientific Research and Management (IJSRM), 2017)
The primary objective of this study was to determine the current state of affairs of organic product suppliers in two 100% ecological bazaars of Istanbul, Turkey. The data were collected by administering a questionnaire to 58 organic product suppliers in 100% ecological bazaars of Sissle and Karta. The results show that the organic farmers have a higher educational level and are younger as compared to the conventional farmers. The primary sources of information about organic farming are other farmers and fellows. Although farmers are satisfied with organic production, it is proposed that more consumers should be aware of the benefits of organic commodities. As local organic bazaars are one of the ways of introducing organic products to consumers, increasing the numbers of such bazaars will contribute both to consumers and producers